Translating uphill cycling into a head-wind and vice versa - Groeskamp, S. (Journal of Science and Cycling, 2017)
Forces acting upon a biker, can be expressed in terms of power (in Watts). Such forces are for example (but not limited to) air-drag, rolling friction and changes in potential energy (due to gravity, when riding up a hill). Here I will specifically compare power related to air drag, with that related to cycling up a hill. This allows me to define the Incline-Equivalent Wind Velocity. The Incline-Equivalent Wind Velocity translates a slope of a mountain into a wind speed, such that overcoming both forces require the same power. Therefore, the Incline-Equivalent Wind Velocity can be interpreted as the velocity with which the wind has to push a rider such that the rider does not roll down a slope of a certain angle, and the net movement is zero. This can be used to recalculate mountain profiles into Incline-Equivalent Wind Velocity profiles and can express the effect of drafting in terms of a reduction in wind speed and incline, rather than power.